Swot Analysis On CIMB Niaga Shari'ah Bank - Nurrachmi, Intan; Azzahra, Fatma (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2025)
This study focuses on a SWOT analysis of CIMB Niaga Syariah Bank, The problems and phenomena raised are the competition between Islamic banks and conventional banks in the digital era, where technological changes encourage banks to innovate to meet the needs of customers who increasingly prioritize digital-based transactions. The purpose of the research is to analyze the marketing strategies used by Bank CIMB Niaga Syariah using SWOT (Strength, Weakness, Opportunity, and Threat) analysis in facing competition in the digital era. The research method used in this study is descriptive qualitative with interview data sources, which aims to collect data directly from relevant sources from Bank CIMB Niaga Syariah. The study uses SWOT analysis to assess the strengths, weaknesses, opportunities, and threats to banks. The results of the research on bank competition in the digital era show that digital transformation has significantly changed the landscape of the banking industry. By leveraging the strength of its large customer base and wide range of market opportunities, the bank was able to increase its market share despite the challenges of well-known competitive brands. This research confirms the importance of innovation and financial skills training for customers or clients to support the growth of banks in the Islamic banking sector.